1995
DOI: 10.1037/0735-7044.109.5.997
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxic lesions of the parabrachial nuclei prevent conditioned taste aversions and sodium appetite in rats.

Abstract: Rats with either electrolytic (Experiment 1) or excitotoxic lesions (Experiment 2) that had been electrophysiologically centered in the gustatory zone of the parabrachial nuclei (PBN) were tested for sucrose and NaCl taste detection thresholds in a conditioned avoidance task. With 1 exception, all of these rats had previously shown severe deficits in acquiring an LiCl-based conditioned taste aversion (CTA) to sucrose, NaCl, or alanine. The rats with excitotoxic lesions also had failed to express a depletion-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 35 publications
8
89
1
Order By: Relevance
“…Such responses are indicative of altered sensory coding of salt taste and this information is conveyed to the second central gustatory relay center, the pontine parabrachial nucleus (PBN). Bilateral lesion of the PBN eliminates salt appetite stimulated by a variety of methods (Hill & Almli 1983, Flynn et al 1991, Spector et al 1993, Scalera et al 1995. However, it is the connections distal to the PBN that are believed to be critical for the expression of salt appetite because decerebrate rats, which have an intact PBN but severed connections to the forebrain, do not express a salt appetite (Grill et al 1986).…”
Section: Central Gustatory Processingmentioning
confidence: 99%
“…Such responses are indicative of altered sensory coding of salt taste and this information is conveyed to the second central gustatory relay center, the pontine parabrachial nucleus (PBN). Bilateral lesion of the PBN eliminates salt appetite stimulated by a variety of methods (Hill & Almli 1983, Flynn et al 1991, Spector et al 1993, Scalera et al 1995. However, it is the connections distal to the PBN that are believed to be critical for the expression of salt appetite because decerebrate rats, which have an intact PBN but severed connections to the forebrain, do not express a salt appetite (Grill et al 1986).…”
Section: Central Gustatory Processingmentioning
confidence: 99%
“…Our neural tracing studies have revealed that the HSD2 neurons primarily innervate rostral brain sites that previously have been implicated in sodium appetite (our unpublished observations), including subnuclei within the pontine parabrachial region (Scalera et al, 1995) and the bed nucleus of the stria terminalis (Reilly et al, 1994;Zardetto-Smith et al, 1994). It also should be noted that small NTS lesions, lateral to the HSD2 neurons and area postrema, eliminate baroreflex regulation of blood pressure and heart rate yet leave sodium appetite intact (Schreihofer et al, 1999).…”
Section: Hsd2 Neurons As a Neuroanatomical Link To Sodium Appetitementioning
confidence: 99%
“…Gustatory responses of PbN neurons to NaCl in sodium-deprived rats were reduced relative to the control animals (70). Lesions of PbN also block the expression of a sodium appetite in rats (14,66), suggesting that PbN is involved in mediating sodium appetite.In addition, studies have demonstrated that lesions of the PbN prevent acquisition of CTA in rats (19,59,69,77,90).A number of anatomical and electrophysiological studies have shown strong neuronal connections between the PbN and forebrain gustatory nuclei. The efferent projections to the gustatory PbN from the LH, CeA, BNST, and GC were demonstrated in rats and hamsters (41,83,84,88,94).…”
mentioning
confidence: 99%